The Adjudication of Customs’ Tariff Classification Disputes in South Africa: Lessons from Australia and Canada - Colesky, Theo; Franzsen, Riël (Comparative and International Law Journal of Southern Africa, 2022)
One of the responsibilities of a customs administration is the collection of customs duties on imported goods. This necessitates the tariff classification of the goods in question. As a result of South Africa’s membership of the World Customs Organization, specific obligations in relation to tariff classification are incurred. Tariff classification is a highly technical and intricate undertaking, subject to both national and international law. Especially the implementation and application of the international provisions result in varying interpretations by stakeholders. This, inevitably, results in disputes. This article discusses the position in South Africa regarding customs tariff classification dispute resolution and compares the South African provisions and practices with those in Australia and Canada. The differences in the approach to dispute resolution in the three countries are critically analysed. In conclusion it is recommended that South Africa should consider introducing an independent tribunal along the lines of the tribunals established in Australia and Canada, or, alternatively, extending the jurisdiction of the Tax Court to include customs duty disputes.